Mosque Based Community Empowerment (Case Study: Jogokariyan Mosque) - Ahmad Danis; Dian Silvia Rozza; Romelah Romelah (At-Ta'dib, 2022)
The function of the mosque in the period of the Prophet Muhammad SAW as the center of Islamic civilization with a good level of prosperity. The mosque at that time had various functions, not only as a place of worship but also as a place of knowledge and as a center of social activities. However, it is very unfortunate because at this time the function of the mosque operates in a strict sense as a ritual of worship. In fact, many mosques are not maintained, so the level of prosperity tends to be below. The existence of the Jogokariyan Yogyakarta Mosque is good news for Muslims. A mosque that grows and develops with programs that modernly seek to empower the congregation and the surrounding community. The Jogokariyan Mosque has been categorized as a civilized and prosperous mosque. Jogokariyan Mosque is a strategic location to carry out the dual functions of hablum minallah and hablum minannas. This means that the mosque is a house of worship and the mosque is empowered as a social house. This study aims to reveal the efforts made by the Jogokariyan Mosque so that the community at large can feel its role. This research utilized descriptive qualitative research with interviews, observations, and literature review as a research reference. From the results of the study, it appears that the Jogokariyan Mosque has an important influence and role in the prosperity of its congregation. This shows that a prosperous mosque will have an effect on the prosperity of its congregation.